STRATEGI PENGEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) KEMBANG GOYANG BUNGA MATAHARI DI KECAMATAN CIBINONG KABUPATEN BOGOR - Tika Kartika Asri; Mujito; Zeze Zakaria Hamzah; I Gusti Ayu Darma Cintia (Economicus : Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the internal factor and external factors of the Kembang Goyang Bunga Matahari Micro, Small, and Medium Enterprise (MSME) and to determine the appropriate development strategy to be implemented. The results of the study show that: (1) based on the results of the IFE matrix calculations, it is known that the highest score on the strength factor is a quality and durable product and an affordable product price with a total score of 3.75 for each. Meanwhile, the highest score on the weakness factor is obtained from limited business capital and insufficient distribution with a total score for each factor of 2. (2) Based on the results of the EFE matrix calculation, the highest score for the opportunity factor is collaborating with local cake shops and government policies that support MSMEs with a total score of 3.75 each. Meanwhile, the highest score for the threat factor is competition from competitors with similar products and product innovations that are easily copied by competitors with a total score of 2 each. (3) Based on the results of the IE matrix, it shows that the position of MSMEs is in the average position of quadrant V, so the strategy needed is to maintain and defend by carrying out market penetration and product development.